Rhizobium–legume symbioses: the crucial role of plant immunity. (March 2015) - Gourion, Benjamin; Berrabah, Fathi; Ratet, Pascal; Stacey, Gary
Highlights Nod factors that elicit legume nodule organogenesis also suppress plant immunity. The rhizobial type III secretion system (T3SS) can influence host range. Resistance gene-mediated immunity can impact upon rhizobial host range. Management of host defenses is also important for the maintenance of symbiosis. The plant growth environment can impact upon plant defense and symbiosis.